Financial planning and financial satisfaction: evidence from individual investors in Jaffna district, Sri Lanka - Kengatharan, L.; Mithushana, R. (ISPEC 7th INTERNATIONAL CONFERENCE ON SOCIAL SCIENCES & HUMANITIES 18-19 Sep, 2021 / MUŞ-TURKEY, 2021)
The study examined the impact of financial planning on the financial satisfaction of individual investors in the Colombo Stock Exchange (CSE). The current study tried to identify whether proper financial planning provides satisfaction to the investors. Participants of the study were selected from investors who took part regularly in the training sessions conducted by the CSE in Jaffna. Convenient sampling was used to select the sample and data were collected from 150 participants using a structured questionnaire. The reliability test, correlation, and regression analysis were carried out for the data analysis. Accordingly, the results of the study revealed that there is a significant positive impact of financial planning on the financial satisfaction of the investors in CSE from the Jaffna district. The impact implies that proper planning of the investors about their investments would lead them towards successful performance in the stock market and therefore their satisfaction also will increase. The study provides more insights to the investors to prepare a plan annually or other time intervals on their financial transactions, especially towards the investment. Further, it can be suggested to the stock exchange such as the Jaffna branch to provide more concern on investor’s financial planning and this would avoid their future failures on stock markets. Future researches can find strategies that drive people towards active participation in stock markets.
Keywords: Financial Planning; Financial Satisfaction; Investors; Jaffna